Hubungan Antara Status Pendidikan Dan Status Pekerjaan Ibu Dengan Status Gizi Anak Usia Prasekolah Di Tk Pelangi Kelurahan Sangkrah Semanggi Surakarta - YULIAWAN, Rizqi, Endang Nur W, S.St., M.Si.Med, Dyah Widowati, SKM (2015)
Background: Preschool children represent the group which susceptible to experience of the nutrient problem. Mother education represent the especial capital in compilation eat the family, mothering and child treatment. One of negativity impact which is felt concerned about at outdoors activity is the lack of construction and child conservancy including the problem of accomplishment of children nutrient satus. Purpose: To decribing and analyzing the correlation between education level and job status mother with nutrient status preschool age children in Pelangi Kindergarden Kids Sangkrah Sub-District Semanggi Surakarta. Method: This research represents observatiobal research with cross sectional study approach. Sample taking tachnique use simple random sampling and get sample account of 48 persons. Measurement mount mother education and mother job status use questioner and nutrient status measured by using weighing-machine and then measure result expressed in z-score. Data analysis technique analyse use Chi Square test. Result: Univariate result analysis known that majority mother have high education that is SMA account of 40 persons (83,3%), majority mother not working account of 27 persons (56,2%) and the child have good nutrient status account of 42 childrens (87,5%). Chi square result analysis known that there is correlation between mother education status with nutrient status preschool age children by p value (0,000) < 0,05 and there is correlation between mother job status with nutrient status preschool age children by p value (0,037) < 0,05.